Investigating of A Modified Model for Human Eye Movement - Abbass, Sadiq Jafer; Baker, Sheelan Kameran (Nahrain University College of Engineering Journal, 2017)
In this research a biological model was modified upon a homomorphic sccadic eye movement model by adding and calculating the mass of eye and the elasticity of eye tendon and take a primary position only. According to this modification, equation with six order was appeared which was processed with a MATLAB SIMULINK to get a desire results of theta, velocity and acceleration in the normal case.For the same model, a disease was estimated to evaluate the results of theta and how it is affected by this disease which was estimate the increase and decrease happened in the primary elastic element and viscosity. After theta controller was added to the model to control the system and get the desire angle which is equal to 15º in the normal case while in the system with disease, the PI controller that used can control only the system during normal case while in the system with disease, the PI controller could not control the system to get the desired angle.